A reinvenção do conto a cartomante, de Machado de Assis, em libras, numa perspectiva transcultural - Nogueira, Mariana Daleprani (2023)
This dissertation aimed to build and execute a literary translation project of the short story A cartomante, by Machado de Assis, into Libras, which favors an attractive literary reading for the deaf public. It was characterized as a bibliographic and applied research, whose main sources were: a) in the first stage, dissertations and theses who focused on the translation of works of Brazilian literature translated into Libras and b) the process of recreating the short story A cartomante into Libras in audiovisual material based on the concepts of cross- cultural translation (SOBRAL, 2019), translation/transcreation (PLAZA) and adaptation (HUTCHEON, 2003). The methodology of description and analysis of the literary recreation data used the procedures of commented translation. The results of the analyzes showed that the recreation of the tale in Libras constituted a translation- adaptation built from various processes of transformation of verbal signs into visual, performative ones linked to the aesthetic principles of deaf culture to make it attractive to the deaf reader. We also found that, in the activity of translation the literary object in Libras, the translator used strategies for reading the source text, creating mental images from the reading and materialization of these images and scenes in the physical body, acting as an actor. Therefore, for a literary translation in Libras, it is essential to know and appropriate knowledge from the field of scenic studies to create poetic performances that communicate actions, feelings, emotions, provoking in the reader an aesthetic experience with the literary body-text.